LAW AND ETHICS OF COMMUNICATION IN SOCIAL MEDIA - Rini Fidiyani; Dewi Sulistianingsih; Pujiono Pujiono (Jurnal Dinamika Hukum, 2017)
Every Environment Has Its Own Laws And Ethics Which Guide Behavior; However, It Does Not Mean That Anybody Is Able To Obey It And It Rises Three Consequences At Legal, Ethic And Social. This Research Is A Quantitative Research With Law In Action Approach, It Is A Non-Doctrinal And Empirical Social Science Study. Internet Brings The World To New Ways Of Thinking, And Communicating. Netiquette Is An Ethical Guide In Behaving / Communicating Among Netizens. Teachers’ Awareness To Communicate Well In Smk Bakti Purwokerto Is At A Poor Level. Bad Habits Communications In Real-World Are Brought Into Cyber Which Often Create Legal Issues. Although No One Has Proceeded To Justice, It Is Quite Worrying Since Their Position As Teachers Should Be Role Models For Their Students. It Is Necessary To Realize The Awareness Of Compliance With The Law And Ethics Of Cyber Communication For These Teachers.Keywords: Netiquette, Internet, Social Media, Law And Ethics, Communication.